The effects of death and post-mortem cold ischemia on human tissue transcriptomes - Pedro G. Ferreira (Nature Portfolio, 2018)
RNA levels in post-mortem tissue can differ greatly from those before death. Studying the effect of post-mortem interval on the transcriptome in 36 human tissues, Ferreira et al. find that the response to death is largely tissue-specific and develop a model to predict time since death based on RNA data.